Rancang Bangun Sistem Informasi Reporting Apotek Rezky Medika (SIRARM) Berbasis Web Menggunakan Laravel 10: Design A Web-Based Rezky Medika Pharmacy Reporting Information System (SIRARM) Using Laravel 10 - cindy aprillia atmaja; Julius Panda Putra Naibaho; Lion Ferdinand Marini (JISTECH: Journal of Information Science and Technology, 2024)
Cindy Aprillia Atmaja. Informatics Engineering. Faculty of Engineering. Design a web-based Rezky Medika Pharmacy Reporting Information System (SIRARM) using Laravel 10. Mentored by Julius P.P. Naibaho and Lion F. Marini. Rezky Medika Pharmacy is one of the pharmacies located on Manokwari, West Papua. Apotek Rezky Medika still relies on a manual system in reporting, managing stock, and managing incoming and outgoing drug data. This manual process has the potential to cause various problems, such as errors in inputting data, and confusion in finding information. In this study, the author designed and built a Web-Based Rezky Medika Pharmacy Reporting Information System Using Laravel 10. Data collection methods include observation, interviews, literature studies, and documentation. As well as application development using Agile methods, through the stages of planning, implementation, software tests, documentation, deployment, and maintenance. By developing a web-based information system, it is expected that Apotek Rezky Medika can improve operational efficiency, increase data accuracy, facilitate access to information, and strengthen its position as a superior and leading pharmacy in service to customers.